Greek teenager patients’ desire for information during the perioperative period - F. Bakalaki; N. Zavras; P. Perdikaris; C. M. Vassalos; M. Polikandrioti; A. Zartaloudi; I. Koutelekos (European Psychiatry, 2023)
Introduction Admission to hospital is a stress-inducing experience for children. Informing children helps to reduce anxiety according to their developmental stage. Objectives To explore the associations between Greek teenager patients’ characteristics and their desired information during the perioperative period. Methods Eighty children (52 boys, 28 girls; median age: 12 years old) admitted for surgery into a large Greek paediatric hospital self-completed a 40-item questionnaire on Children’s Desire for (perioperative) Information (CDI). The respondents’ desire for perioperative information was calculated by summing responses (‘I really have to know’ plus ‘I might want to know’) to all 40 items. Ethical issues were addressed. We used multiple linear regression to explain the relationship between participants’ characteristics (demographic, attitudes, coping strategies) and their desire for information when facing surgery. A p value of less than 0.05 was considered statistically highly significant. SPSS 21.0 was used for statistical analysis. Results